Engagement in meaningful activities post suicide loss: A scoping review protocol. - Monique Gill; Meera Premnazeer; Orianna Scali; Sakina Rizvi; Alex Schendelman; Helene Polatajko; Jill I Cameron (PLoS ONE)
Rationale Each day, more than 10 Canadians die by suicide. Each suicide leaves entire communities to manage the traumatic aftermath of this loss. Individuals bereaved by suicide loss are at a higher risk of experiencing negative mental health outcomes. Current research suggests that engagement in meaningful activities may be an avenue to protecting mental health. It is important to understand if this is also the case for those experiencing bereavement post suicide loss. To date, there has not been a synthesis of the literature examining suicide loss and the nature and extent of engagement in meaningful activities post loss. Objectives 1) To describe the nature and extent of the peer-reviewed suicide loss and bereavement literature related to engagement in meaningful activities; and 2) to identify facilitators and barriers that may impact engagement in meaningful activities post loss. Methods This paper describes a scoping review protocol that will be completed using stages identified by Arksey and O'Malley and updated by Levac and colleagues. Joanna Briggs Institute framework will also guide this review. Four electronic databases will be searched for suicide bereavement/loss concepts. Two reviewers will apply inclusion and exclusion criteria to identify articles discussing engagement in meaningful activities of everyday living post loss. Data will be descriptively summarized and analyzed using inductive content analysis. Results will be reported following PRISMA Extension for Scoping Reviews. Expected results A descriptive summary and conceptual map describing the current state of the peer-reviewed literature will be constructed. Conclusion Experiencing a suicide loss increases the risk of negative mental health outcomes. A synthesis of literature is required to map the current available evidence related to suicide bereavement and engagement in meaningful activities, with potential implications for improving supports and services for those bereaved. This protocol is register with Open Science Framework Registries (10.17605/OSF.IO/M2NES).